Electronic design automation : synthesis, verification, and test - Wang, Laung-Terng; Chang, Yao-Wen, 1966-; Cheng, Kwang-Ting, 1961- (Morgan Kaufmann/Elsevier, 2009)
This book provides broad and comprehensive coverage of the entire EDA flow. EDA/VLSI practitioners and researchers in need of fluency in an ""adjacent"" field will find this an invaluable reference to the basic EDA concepts, principles, data structures, algorithms, and architectures for the design, verification, and test of VLSI circuits. Anyone who needs to learn the concepts, principles, data structures, algorithms, and architectures of the EDA flow will benefit from this book. Covers complete spectrum of the EDA flow, from ESL design modeling to logic/test synthesis, verific.
Keywords: Electronic circuit design -- Data processing.; Computer-aided design.; elektronické knihy; electronic books